Unravelling genetic heterogeneity of hepatocellular carcinoma with driver genes and subclones - Ng, Ming Hwee (2015)
Integration of genetic studies in hepatocellular carcinoma (HCC) is lacking though its mortality rate has risen to the second highest. With 1186 samples from varying ethnicities, this study had collected the largest sample size to compile a catalog of HCC cancer genes with MutSigCV and 37 novel genes were discovered. Further increment of sample size would be valuable to build on a complete catalog, especially for driver genes that were mutated in less than 2% of samples. The driverness index of the driver genes was investigated to decipher the sole actionable drive of a cancer gene. Most driver genes required the complementation of another driver gene in tumorgenesis. This is true for CTNNB1 and TP53, which had been mutated in more than 300 samples and for AXIN1, which had been mutated in 68 samples. The clonality analysis next, determined if driver genes were found in all or a subset of a tumor and thus whether it was an early or late event in tumor evolution. It was concluded that most driver genes occurred as an early event. The genetic landscape of driverness and clonality in driver genes was drawn out in this study to unravel intratumor genetic heterogeneity and to further understand tumor evolution.